'J' brachioplasty technique in massive weight loss patients. Issue 5 (3rd September 2018) - Bocchiotti, Maria A.; Ruka, Erind; Spaziante, Luca; Morozzo, Umberto; Baglioni, Elisabetta A.; Bruschi, Stefano
Abstract: Upper extremity body reshaping is a very frequent surgical procedure in massive weight loss patients. Many surgeons have presented different patterns of brachioplasty skin excision and a variety of adjunctive techniques, each of them claiming improvements in scar aesthetic, arm shape or overall safety of the procedure. In this pape, r we want to illustrate our personal brachioplasty technique for massive weight loss patients. Our incision design named 'J' Brachioplasty is described. Between March 2013 and March 2016, a retrospective study of patients with massive weight loss and clinical diagnosis of brachial ptosis undergoing surgical reconstruction with 'J' brachioplasty was performed. All patients were treated according to a standard surgical procedure described in detail in the paper. The presence of axillary and thoracic skin excess was also recorded for every subject, as well as clinical and surgical postoperative complications. A total number of 73 Caucasian underwent J-shaped brachioplasty. Our technique allowed us to treat both arm and thoracic skin excess with a single skin incision. Among our casuistic we had only two cases of postoperative bleeding and four cases of partial wound dehiscence due to tension. Seroma was reported only in one (female) patient. Despite the recent introduction our technique has proven to reach good results in massive weight loss patients.